Fostering hybrid team performance through inclusive leadership strategies - Hincapie, M. X.; Costa, P. (Organizational Dynamics, 2024)
Over the past years, hybrid teams have emerged as a prevalent phenomenon in the new work arrangements. Effective inclusive leadership strategies are essential for leveraging the full potential of hybrid teams, fostering collaboration, achieving high performance, and improving team members’ well-being. Hybrid teams have members who frequently shift between co-located and remote working. This makes them face unique challenges with technology-mediated communication (e.g., trust development) and the leaders' need to balance the preferences and needs of co-located and remote team members. Leaders must ensure that all team members feel valued and included, regardless of location or schedule, in order to achieve team objectives and enhance well-being. This paper explores hybrid team leaders’ challenges in managing diversity, equity, and inclusion, offering evidence-based strategies and practical recommendations. Specifically, we emphasize strategies for building trust and psychological safety, leveraging diversity as a strength, promoting cross-cultural understanding, establishing clear communication channels, and encouraging collaboration. By empowering hybrid team leaders with these insights, the aim is to foster a culture of inclusion and create an environment where all team members feel valued, ultimately leading to enhanced individual and team performance and team member well-being.